2021
DOI: 10.9734/ajb2t/2020/v6i430087
|View full text |Cite
|
Sign up to set email alerts
|

The Advances of Plant Product Meat Alternatives as a Healthier and Environmentally Friendly Option for Animal Meat Protein Consumption

Abstract: High protein from meat consumption has been associated recently to environmental depletion and health related issues despite the important contribution of meat and meat products in diet and growth development. This has motivated debates on a drastic shift from excessive meat consumption amongst stake holders, academics, animal rights activists and environmentalist as informed consumers are pushing food scientist for a more sustainable alternative protein source. Plant proteins are considered a suitable alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Nowadays, red pigments are added like beet juice or soy leghemoglobin called "heme" (Fraser et al, 2017;Lee et al, 2020;Vrljic et al, 2014) to impart meat-like appearance and flavor especially during cooking. As discussed below, there are several texturization processes (Table 2) available to create the wholemuscle or fibrous structure from plant-based proteins (Dekkers et al, 2018;Fonmboh et al, 2021;Kyriakopoulou et al, 2019).…”
Section: Methods Of Texturizing Plantbased Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, red pigments are added like beet juice or soy leghemoglobin called "heme" (Fraser et al, 2017;Lee et al, 2020;Vrljic et al, 2014) to impart meat-like appearance and flavor especially during cooking. As discussed below, there are several texturization processes (Table 2) available to create the wholemuscle or fibrous structure from plant-based proteins (Dekkers et al, 2018;Fonmboh et al, 2021;Kyriakopoulou et al, 2019).…”
Section: Methods Of Texturizing Plantbased Proteinsmentioning
confidence: 99%
“…Meat alternatives, also termed meat substitutes, fake meat, mock meat, imitation meat, or meat analogs, are products which share aesthetic and physicochemical properties such as taste, texture, aroma, and mouthfeel with real meat (Fonmboh et al, 2021;Ismail et al, 2020;Joshi & Kumar, 2016;Sha & Xiong, 2020). A number of texturization methodologies have been employed to generate the meat-like fibrous structure and fleshy appearance of plant-based meat products.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated the use of wet spinning technology as a common method to produce food-grade fibers from soy, pea, and faba beans ( Grossmann and Weiss, 2021 ). Electrospinning is another potential technology for the formulation of textures on nanofiber level ( Fonmboh et al., 2021 ), however, such applications are rather limited to the specific cases, where the inclusion of specific substances (polyphenols or probiotics) in food matrix is required. More industrially applicable are “top-down” techniques applicable to plant protein concentrates and isolates (soy, wheat, pea, lupine, rapeseed, etc.)…”
Section: Environmental Impact and Resource Use Of Alternative Protein...mentioning
confidence: 99%